Pengaruh ROA, DER, EPS, PER, DAN PBV Terhadap Harga Saham - Nerissa Arviana; Narumi Lapoliwa (Ultima Accounting : Jurnal Ilmu Akuntansi, 2013)
The purpose of this research was to analyze the effect of financial ratio towards share price. Financial ratio can be used by investor to analyze the share price before investor made an investment decision. Financial ratio used in this research were profitability ratio measured by return on assets and earning per shares, solvability measured by debt to equity ratio, and market ratio measured by price earning ratio and price to book value. The samples used in this research were 25 companies. These samples were the companies that listed at Indonesia Share Exchange (IDX) for period 2009 until 2011 and meet the criteria sampling of this study. The samples were determined based on purposive sampling method. Data that used in this research was secondary data, such as share price and financial reports. The results of this research were (1) there were significant effect of debt to equity ratio, earning per shares, and price book to value ratio towards share price (2) there was no significant effect of return on assets and price earning ratio towards share price. Keyword: Debt to Equity Ratio, Earning Per Share, Financial Ratio, Price Earning Ratio, Price to Book Value, Return On Assets, Share Price